2015
DOI: 10.1089/thy.2015.0211
|View full text |Cite
|
Sign up to set email alerts
|

Metformin Does Not Suppress Serum Thyrotropin by Increasing Levothyroxine Absorption

Abstract: Background: Levothyroxine (LT4) absorption is affected by concomitant ingestion of certain minerals, medications, and foods. It has been hypothesized that metformin may suppress serum thyrotropin (TSH) concentrations by enhancing LT4 absorption or by directly affecting the hypothalamic-pituitary axis. This study examined the effect of metformin ingestion on LT4 absorption, as assessed by serum total thyroxine (TT4) concentrations. Methods: A modified Food and Drug Administration LT4 bioequivalence protocol was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…In a prospective study, increased metformin use was associated with low TSH levels among patients with treated hypothyroidism but not those with normal thyroid function [ 22 ]. A study by Al-Alusi et al shows that metformin suppressed serum TSH levels independent of increasing levothyroxine absorption [ 23 ]. Cappelli et al found a significant decrease in TSH levels in euthyroid patients with higher baseline TSH concentrations after metformin therapy [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a prospective study, increased metformin use was associated with low TSH levels among patients with treated hypothyroidism but not those with normal thyroid function [ 22 ]. A study by Al-Alusi et al shows that metformin suppressed serum TSH levels independent of increasing levothyroxine absorption [ 23 ]. Cappelli et al found a significant decrease in TSH levels in euthyroid patients with higher baseline TSH concentrations after metformin therapy [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In most studies, there was no increase of serum thyroid hormone level in response to metformin, irrespective of thyroxin replacement or not. A clinical study concluded that levothyroxine (l-T 4 ) absorption is unchanged by concomitant metformin intake (Al-Alusi et al 2015). In addition, metformin is not known to increase the absorption of any other nutrients or drugs.…”
Section: :1mentioning
confidence: 99%
“…They cannot be also related to the effect on levothyroxine absorption, which has not been affected by concomitant metformin ingestion. 27 Finally, similar baseline and posttreatment values of the body mass index and waist circumference are an argument against their association with a weight-reducing effect of metformin, as suggested by Casteràs et al 22 In case of metformin, this association may be explained by metformin action on adenosine 5 0monophosphate-activated protein kinase, which both regulates energy homeostasis and glucose balance, 28 and directly affects thyrotropin and other pituitary hormone secretion. 29 In turn, myo-inositol modulates the glycosyl phosphatidylinositol/inositol phosphate glycan signalling pathway, acting as a messenger of thyrotropin and insulin action.…”
Section: Discussionmentioning
confidence: 92%
“…However, at the beginning of the current study, glucose homeostasis markers did not differ between the study groups and therefore differences in insulin‐sensitizing potencies of metformin and myo‐inositol cannot explain our findings. They cannot be also related to the effect on levothyroxine absorption, which has not been affected by concomitant metformin ingestion 27 . Finally, similar baseline and post‐treatment values of the body mass index and waist circumference are an argument against their association with a weight‐reducing effect of metformin, as suggested by Casteràs et al 22 In case of metformin, this association may be explained by metformin action on adenosine 5′‐monophosphate‐activated protein kinase, which both regulates energy homeostasis and glucose balance, 28 and directly affects thyrotropin and other pituitary hormone secretion 29 .…”
Section: Discussionmentioning
confidence: 99%